Prevalence and Intensity of Anchor Worm (Lernaea cyprinacea L.) Ectoparasite in Koi Fish (Cyprinus carpio L.) at Bantul Koi Farm D.I. Yogyakarta - Afriandini, Wida; Suwartiningsih, Nurul (Journal of Biotechnology and Natural Science, 2021)
One obstacle in the cultivation of Koi fish (Cyprinus carpio L.) in Bantul Koi Farm D.I. Yogyakarta is a disease caused by parasites of anchor worms (Lernaea cyprinacea L.). Therefore, this study observed the prevalence and intensity of anchor worm ectoparasites in Koi fish in Bantul Koi Farm. Taking fish samples using the purposive sampling technique. Each of three fish individuals was taken as replication from three populations, namely Showa, Shiro and Saragoi, with a size of 28-36 cm. The prevalence and intensity are determined by the observation method by counting the number of anchor worms found. Inferential statistics carried out data analysis of the number of ectoparasites in each population. The results showed that the highest anchor tick ectoparasite prevalence was found in the Shiro population (100%) and the lowest in the Saragoi population (33%). The highest intensity was in the Showa population (4 individu/ fish), and the lowest was in the Shiro population (2 individu/ fish), although all of them were in a low category. The highest number of ectoparasites was obtained from the Showa population (8 individuals) and the lowest in the Saragoi population (3 individuals), but it was not statistically significant. The high prevalence in the Shiro population is due to the high stocking density. Anchor flea ectoparasites attacked the skin and fins of Koi fish and were not found to attack gills. The conclusion of this study is the highest prevalence of anchor tick ectoparasites was found in the Shiro population (100%) and the lowest in the Saragoi population (33%). The highest intensity was found in the Showa population (4 individu/ fish) and the lowest in the Shiro population (2 individu/ fish), even though all of them were in a low category.